Two new species of the tribe Xylographellini (Coleoptera: Ciidae) from Yunnan Province, China - Mo, Da-Rui; Xu, Ji-Shan (Zootaxa, 2022)
Two new species of the tribe Xylographellini, Syncosmetus wuliangensis sp. nov. and Scolytocis multispinus sp. nov. are described and illustrated from Yunnan Province, China. Key to all known species of the genus Syncosmetus, and the key to the Australian and Oriental species of the genus Scolytocis are updated to include the two new species.